Medical research and reproductive medicine in an ethical context: a critical commentary on the paper dealing with uterine lavage published by Munné et al - Murtinger, Maximilian; Wirleitner, Barbara; Hradecký, Libor; Comploj, Giorgio; Okhowat, Jasmin; Spitzer, Dietmar; Stadler, Jürgen; Haidbauer, Robert; Schuff, Maximilian; Yildirim, Selma; Soepenberg, Therese; Eibner, Kerstin; et al. (Journal of assisted reproduction and genetics, 2020)
A recent study published in Human Reproduction claimed that uterine lavage offers a non-surgical, minimally invasive strategy for the recovery of human embryos from fertile women who do not want or need IVF for medical reasons but who desire preimplantation genetic testing (PGT) for embryos. To prove this hypothesis, the researchers recruited dozens of young Mexican women. The prospective oocyte donors underwent ovarian stimulation to induce the production of multiple mature oocytes. Subsequently, these women were inseminated by donor semen. A few days later, the developing embryos were collected by uterine lavage (uterine flushing) and subjected to genetic testing for aneuploidies (PGT-A). Oocyte donors with persistently elevated hCG levels, indicating the implantation of one or more embryos after uterine lavage, had to undergo uterine curettage and/or treatment with methotrexate. A critical opinion paper discussing the aforementioned study was published by De Santis and colleagues and has raised critical issues that are largely technical in nature. However, this opinion paper neglects-from our point of view-critical issues of the Mexican study regarding ethical principles and moral standards in human research. These aspects are summarized below.
Keywords: biomedicínský výzkum; dospělí; Preimplantation Diagnosis; Uterine lavage; PGT-A; Female; Embryo Transfer; aneuploidie; fertilizace in vitro; přenos embrya; Adult; ženské pohlaví; Semen; Oocytes; Publication standards; Oocyte Retrieval; lidé; těhotenství; oocyty; Ethics; implantace embrya; sperma; reprodukční lékařství; Oocyte donors; odběr oocytu; Male; Embryo Implantation; preimplantační diagnóza; Reproductive Medicine; mužské pohlaví; Aneuploidy; Pregnancy; Biomedical Research; Fertilization in Vitro; Humans